Evaluación técnico-financiera a nivel laboratorio de un fluido de perforación base agua para la perforación de un pozo en el campo Níspero (2017)
The present work of degree is realized in order to design a fluid of Water based drilling with the ability to inhibit reactive shales present During the drilling of the 12 ¼ "middle section of a well in the Field Níspero located in the Lower Valley Magdalena Basin, which generate a An unfavorable reaction when in contact with the fluid. For this purpose, it is decided to perform the characterization of the 14 rock samples Obtained from the perforation of the intermediate section 12 ¼ "of the Níspero-1 Well.